Training of Future Musical Art Teachers: An Ethnocultural Approach - Yeremenko, Olha; Chystiakova, Iryna; Biriukova, Larysa; Petrenko, Maryna (Journal of History Culture and Art Research, 2020)
The article reveals theoretical and methodological foundations of implementing the ethnocultural approach in the process of future musical art teachers’ professional training. The results of the study have shown that implementing the ethnocultural approach in art education is one of the requirements of the new education paradigm. It is proved that in the process of future musical art teachers, professional training should be taken into account the developmental capabilities of folk music and peculiarities of ethno-musical education development. The article highlights the principles, which regulate the process of future musical art teachers’ professional training: ethnocultural basis of students’ professional skills formation; using national samples of musical art as learning repertoire; involving students in various types of musical and aesthetic activities, especially in the study of various works of national musical art; personality-centered organization of the educational process; inclusion of ethnocultural component in courses of historical-theoretical and methodological cycles; effective use of various forms of ethno-musical activity.